Analysis of Senior High Schools Quality in Banda Aceh Using Cluster and Correspondence Analysis - Yulia Zahara; Fitri Ayu Ningtiyas; Nurul Afni Sinaga; Rifaatul Mahmuzah; Hidayatsyah Hidayatsyah (Study Program of Mathematics Education of Unimed Postgraduate Program, 2023)
The purpose of this research is to analyze the relationship between teachers and school conditions on school test scores. Correspondence and cluster analysis are the analytical methods used. For school conditions to be classified into 3 clusters, 4 clusters, and 5 clusters, cluster analysis is used. The variable is tested using the G test to determine the affect on school test scores. This study resulted in a variable that has an impact on school test scores, school conditions with a p-value < α, so a correspondence analysis plot was formed to show the correlation between school conditions and school test scores. Good school conditions will result in good school test scores. Meanwhile, a reasonably good school conditions will result in fairly good school test scores. The correlation of school test scores with teachers shows that good school test scores are resulted by teachers with very good quality. Fairly good school test scores are resulted by good and fairly good teachers. Meanwhile, poor school test scores are resulted by teachers with poor quality. Keywords: School test scores, teacher, school conditions, correspondence analysis, and cluster analysis.